Factors Associated with Dental Fear and Anxiety in Children Aged 7 to 9 Years - Andreas Dahlander; Fernanda Soares; Margaret Grindefjord; Göran Dahllöf (MDPI AG, 2019)
The aim was to investigate changes in dental fear and anxiety (DFA) and verify factors associated with DFA in children. A longitudinal cohort study that included 160 children aged 7 years was carried out. A questionnaire was completed by parents at two time points and evaluated the immigrant background, maternal education, whether the child had ever had toothache, and whether the parents had dental fear. The oral clinical examination evaluated decayed, extracted, and filled primary teeth (deft). The children’s fear survey schedule dental subscale (CFSS-DS) was used to assess the dental fear of the children. Multilevel mixed-effects logistic regressions analyses were used. The CFSS-DS found that 7% of the children had dental fear at age 7 and mean CFSS-DS was 22.9. At 9 years of age, 8% reported dental fear and the mean increased to 25.4. Parental dental fear, experience of toothache, and report of painful dental treatment and caries development between 7 and 9 years of age were factors that were significantly related to development of DFA. There was a change in DFA between 7 and 9 years of age. Dental fear and anxiety is a dynamic process in growing individuals and is significantly related to painful symptoms and experiences of dental care as well as parental dental fear.